2010
DOI: 10.1111/j.1365-2966.2010.17136.x
|View full text |Cite
|
Sign up to set email alerts
|

Host galaxy colour gradients and accretion disc obscuration in AEGIS z ∼ 1 X-ray-selected active galactic nuclei

Abstract: We describe the effect of active galactic nucleus (AGN) light on host galaxy optical and UV‐optical colours, as determined from X‐ray‐selected AGN host galaxies at z∼ 1, and compare the AGN host galaxy colours to those of a control sample matched to the AGN sample in both redshift and stellar mass. We identify as X‐ray‐selected AGNs 8.7+4−3 per cent of the red‐sequence control galaxies, 9.8 ± 3 per cent of the blue‐cloud control galaxies and 14.7+4−3 per cent of the green‐valley control galaxies. The nuclear c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 102 publications
(222 reference statements)
0
8
0
2
Order By: Relevance
“…The distinct difference between the locations of the AGNs and the optically selected galaxy populations in the CMD implies that distant AGNs are found in a subset of the galaxy population and, tentatively, suggests that they are the catalysts for the transition of galaxies from the blue cloud to the red sequence (e.g., through the suppression of star formation via energetic winds, outflows, and jets; see Veilleux et al 2005;Fabian 2012 for reviews). However, later studies showed that clear distinctions between the host-galaxy colors of the AGN and the galaxy populations mostly disappear when the galaxy sample is matched in mass to the AGN sample (e.g., Silverman et al 2009b;Xue et al 2010;Pierce et al 2010b;Rosario et al 2013b), with broadly similar fractions of coeval galaxies and AGNs found in the red sequence, green valley, and blue cloud out to at least z ≈ 3.…”
Section: Host-galaxy Masses and Colorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinct difference between the locations of the AGNs and the optically selected galaxy populations in the CMD implies that distant AGNs are found in a subset of the galaxy population and, tentatively, suggests that they are the catalysts for the transition of galaxies from the blue cloud to the red sequence (e.g., through the suppression of star formation via energetic winds, outflows, and jets; see Veilleux et al 2005;Fabian 2012 for reviews). However, later studies showed that clear distinctions between the host-galaxy colors of the AGN and the galaxy populations mostly disappear when the galaxy sample is matched in mass to the AGN sample (e.g., Silverman et al 2009b;Xue et al 2010;Pierce et al 2010b;Rosario et al 2013b), with broadly similar fractions of coeval galaxies and AGNs found in the red sequence, green valley, and blue cloud out to at least z ≈ 3.…”
Section: Host-galaxy Masses and Colorsmentioning
confidence: 99%
“…A number of different approaches for measuring host-galaxy morphologies have been developed (e.g., automated classifications based on the distribution of light in the galaxy, two-dimensional fits to the surface brightness profiles to provide disk/bulge decompositions, and human "eyeball" classification), which appear to give broadly similar results (e.g., Huertas-Company et al 2014). The contribution of the AGN to the optical emission can significantly bias morphological measurements (e.g., Simmons and Urry 2008;Pierce et al 2010b) and, therefore, the majority of the studies focus on optically obscured or intrinsically weak AGNs. Fig.…”
Section: Host-galaxy Morphologiesmentioning
confidence: 99%
“…Green colors can also just be an indication of a mixture of old and new stellar populations and not necessarily a "transition" between the two population. Further, recent studies that mass-match non-AGN galaxy samples to AGN host galaxies reveal that the difference in optical colors virtually disappear (Silverman et al 2009;Pierce et al 2010;Rosario et al 2013a,b) Far-infrared (FIR) emission (λ > 40µm) is essentially immune to reddening effects while also being a direct tracer of recent star formation. Dust in the galaxy is heated by UV photons from recently formed OB stars, that then reemit in the mid-far infrared regime (Draine 2003) creating a strong correlation between the FIR luminosity and SFR of a galaxy (Kennicutt 1998;Kennicutt & Evans 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A Gaussian stellar mass (M * ) distribution was used with M min * = 10 9.5 M ⊙ and M max * = 10 12 M ⊙ . The average M * was set at 10 10.9 M ⊙ with a standard deviation of 0.4 dex, in agreement with the sample of X-ray selected, z ∼ 1 AGN hosts presented by Pierce et al (2010). It is assumed that the mass-to-light ratio of the host galaxy is constant within each waveband and thus the host galaxy flux scales linearly with the host M * .…”
Section: Methodsmentioning
confidence: 99%
“…According to Figure 6 of Pierce et al (2010), type 1 and type 2 AGN tend to be found in the 0.55 < U-B < 1.4 and -23.5 < M B < -19 region of the CMD. This region of the CMD is well populated by the model adopted here as many combinations of AGN L X and host galaxy M * fit this criteria.…”
Section: Unified Model Of Agn Hostsmentioning
confidence: 99%